PENDAMPINGAN PERENCANAAN DETAIL ENGINEERING DESIGN PADA PEMBANGUNAN DINDING PENAHAN TANAH SUNGAI ENIM - Deta Mediana, M. Sang Gumilar Panca Putra; Deta Mediana, Nita Anggraini; Dwi Wahyuni; M. Thery Kesuma Pratama; Muhammad Ilham Kurniawan; M. Rafli Ishamuddin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
The development of infrastructure along riverbanks is a strategic measure to reduce the risk of erosion and landslides, particularly in tropical regions like Indonesia. The high rainfall and strong river currents in hilly and mountainous areas increase the potential for erosion and landslides, which pose a risk to local communities. Therefore, a retaining wall (DPT) designed with precise technical methods is needed to prevent such natural disasters. This community service activity aims to provide technical assistance in the preparation of a Detailed Engineering Design (DED) for the construction of a retaining wall along the Enim Riverbank. Through a series of field surveys, technical analyses, and discussions with various stakeholders, a DED was prepared that includes structural design, material selection, and appropriate implementation methods. The analysis results show that a retaining wall with a height of 4 meters, a foundation thickness of 0.7 meters, and a wall thickness of 0.5 meters can be applied at the project site. With the involvement of the community and related parties, this project is expected to reduce disaster risk and enhance the safety of the surrounding environment.